Discourse on Mangkunegara IV Javanese Islamic Spiritual Leadership - Zuhri, Amat (JURNAL PENELITIAN, 2018)
This study aims to analyze the concepts and patterns of spiritual leadership according to Serat Wedhatama, especially the ethical, ascetic and mystical potential of Mangkunegara IV Javanese Islamic spiritual leadership. In the context of civilizations and the treasure of Javanese Islamic literatures, just to have the properties as a warrior is not enough for a leader; one must also have the properties as a clergyman, or having Spiritual Leadership within oneself. Spiritual Leadership has become one of the materials to teach (piwulang) a prince, a future king or a ruler. The basis of this study is Serat Wedhatama by Mangkunegara IV which contains sublime teaching (piwulang luhur) which must be a guide for a leader. This study is a qualitative research. The data is obtained from Serat Wedhatama. Data were analyzed by descriptive method, with a scientific perspective of Sufism and hermeneutics. This study found that Serat Wedhatama teaches that a leader must adhere to the ethical, ascetic and mystical dimensions. The ethical dimension includes the behavior of a leader towards the community. Meanwhile, the ascetic dimension includes the inner attitude of a leader in order to purify his soul. And the ascetic dimension includes the form of the relationship between a leader and God.